PENGEMBANGAN APLIKASI ANALISIS KORELASI BERBASIS EXCEL (STUDI KASUS: PENGARUH PERTUMBUHAN PENDUDUK TERHADAP TINGKAT PENGANGGURAN) - Abdullah Afdhol Richsan; Yahfizham Yahfizham (Jurnal Lebesgue : Jurnal Ilmiah Pendidikan Matematika, Matematika dan Statistika, 2023)
The purpose of this research is to develop an Excel-based Correlation Analysis application that can be used by students, lecturers, and researchers as an alternative that can be used to carry out tests by making it easier for users to analyze and draw conclusions. This research was conducted using the Research and Development (R&D) method to produce products through a development process with a 4D development model which includes Define, Design, Develop, Disseminate. The instruments used were expert validation sheets and student questionnaires. Based on the assessment of the application developed, the results of the expert validation obtained an average value of 3.80 or a percentage of 94.44% which is included in the very valid category. The results of a limited scale trial of 5 final year students showed results with an average percentage of 93.5% which was included in the very practical category and deserved to be disseminated. Furthermore, the application is implemented directly to real problems with a case study of the effect of population growth on the unemployment rate in the city of Medan and btained the result that the correlation between the effect of population growth (X) and the number of open unemployment (Y) in the city of Medan is very strong, where the rxy value is 0.82 and the effect between the X variable on the Y variable is 66.7377% with a ttable value of 2.78 and tcount of 3 so that the correlation is significant.